If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 3u + -14 Reorder the terms: 13 = -14 + 3u Solving 13 = -14 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 13 + -3u = -14 + 3u + -3u Combine like terms: 3u + -3u = 0 13 + -3u = -14 + 0 13 + -3u = -14 Add '-13' to each side of the equation. 13 + -13 + -3u = -14 + -13 Combine like terms: 13 + -13 = 0 0 + -3u = -14 + -13 -3u = -14 + -13 Combine like terms: -14 + -13 = -27 -3u = -27 Divide each side by '-3'. u = 9 Simplifying u = 9
| ln(x+3)=0.8 | | 0.666666666667x+6=0.5x+0.25x | | 2(4e)=90 | | 5+.1q=20-.2Q | | (3(42.5)+y+10)+(42.5+y)=180 | | 12+4(z-3)=-3z+6 | | 5w+11=96 | | 2x+2y+1+3x+1=180 | | (A+p)(a^2-ap+p^2)= | | 2(4e)=20 | | 24=4y-16 | | 2x+8+74+5x= | | 2(x+7)+3x=-4 | | 20.6+2.7x=-8.2x | | 15a*2+26a*2+a*2= | | 4x^2-29x=-3x^2-4x-12 | | 0.75=x+1.75 | | (3x+y+10)+(x+y)=180 | | (8y+7)(8y+27)=0 | | 4(3x-2)=6(4x-2) | | 27=5+9(x+8) | | 7+2(b-3)=-9 | | 2x^2-6x-8=8 | | x(5x+3)=2x^2-5x+3 | | 62-x=281 | | -7-9x=-61g | | x=13/8 | | 0.2(4x+32)=0.8(x+8) | | 2-x+9=8 | | 151-y=260 | | 13/8= | | -4+y=-0.5x |